Differences between mesial and neocortical magnetic-resonance-imaging-negative temporal lobe epilepsy - Doležalová, Irena; Brázdil, Milan; Chrastina, Jan; Hemza, Jan; Hermanová, Markéta; Janoušová, Eva; Pažourková, Marta; Kuba, Robert (Epilepsy & behavior, 2016)
OBJECTIVE: The aim of this study was to assess clinical and electrophysiological differences within a group of patients with magnetic-resonance-imaging-negative temporal lobe epilepsy (MRI-negative TLE) according to seizure onset zone (SOZ) localization in invasive EEG (IEEG). METHODS: According to SOZ localization in IEEG, 20 patients with MRI-negative TLE were divided into either having mesial SOZ-mesial MRI-negative TLE or neocortical SOZ-neocortical MRI-negative TLE. We evaluated for differences between these groups in demographic data, localization of interictal epileptiform discharges (IEDs), and the ictal onset pattern in semiinvasive EEG and in ictal semiology. RESULTS: Thirteen of the 20 patients (65%) had mesial MRI-negative TLE and 7 of the 20 patients (35%) had neocortical MRI-negative TLE. The differences between mesial MRI-negative TLE and neocortical MRI-negative TLE were identified in the distribution of IEDs and in the ictal onset pattern in semiinvasive EEG. The patients with neocortical MRI-negative TLE tended to have more IEDs localized outside the anterotemporal region (p=0.031) and more seizures without clear lateralization of ictal activity (p=0.044). No other differences regarding demographic data, seizure semiology, surgical outcome, or histopathological findings were found. CONCLUSIONS: According to the localization of the SOZ, MRI-negative TLE had two subgroups: mesial MRI-negative TLE and neocortical MRI-negative TLE. The groups could be partially distinguished by an analysis of their noninvasive data (distribution of IEDs and lateralization of ictal activity). This differentiation might have an impact on the surgical approach.
Keywords: Infant; dospělí; mozek; pozitronová emisní tomografie; předškolní dítě; retrospektivní studie; Brain; Epilepsy, Temporal Lobe; Humans; věk při počátku nemoci; Magnetic Resonance Imaging; Young Adult; spánkový lalok; epilepsie temporálního laloku; Positron-Emission Tomography; magnetická rezonanční tomografie; mladý dospělý; elektroencefalografie; Neocortex; fluorodeoxyglukosa F18; mužské pohlaví; Fluorodeoxyglucose F18; Child, Preschool; Adult; neurochirurgické výkony; Adolescent; neokortex; záchvaty; výsledek terapie; Electroencephalography; Seizures; Temporal Lobe; Treatment Outcome; ženské pohlaví; Neurosurgical Procedures; lidé; mladiství; radiofarmaka; Age of Onset; dítě; Child; Radiopharmaceuticals; Male; Retrospective Studies; kojenec; Female